PENGARUH KUALITAS PELAYANAN TERHADAP PENINGKATAN PENERIMAAN RETRIBUSI DAERAH (Studi pada Dinas Perindustrian dan Perdagangan Kabupaten Konawe Selatan) - La Ode Aslim (Universitas Halu Oleo, 2018)
Effect of Service Quality on Increasing Regional Retribution Receipts (Study on the Department of Industry and Trade of South Konawe Regency).The purpose of the study was to find out and analyze the effect of service quality on the reception of regional retribution and analyze the significance of the effect of service quality on the receipt of regional retribution. This research is explanatory research using survey design. The population of this study amounted to 456 people, consisting of elements of service providers and the public who were registered as mandatory industrial registration marks and company registration marks. The research sample was 64 people, consisting of 32 officers and 32 community members. The sampling technique used is simple random using the lottery system. Field data collection is done using questionnaires, interviews, and documentation. To test the research hypothesis used inferential statistical analysis with correlation procedures and simple linear regression.The results showed that service quality has a positive effect on the receipt of regional retribution. However, not all officials are able to provide services based on the principles of reliability, responsiveness, certainty, empathy, and physical evidence. This is due to the existence of constraints, especially: (a) how to provide inappropriate services, (b) the slow pace of initiative by the authorities in resolving community problems, (c) the apparatus is often not timely, (d) the service process discriminates , (e) the discriminatory attitude of the apparatus in the face of different citizens' status, (f) the limitations of service operational facilities, and (g) the absence of a service flow chart. Service quality has a big influence on the receipt of regional retribution. Maximum achievement in the ratio of the effectiveness of regional levies receipts, and the tendency to increase the effectiveness of regional levies receipts occurred mainly as a direct result of the quality of services provided by the District Office of Industry and Trade of Konawe Selatan.